ANALISIS PENGALAMAN PERAWAT IPCN DALAM PELAKSANAAN PROGRAM PPI DI RSU VITA INSANI PEMATANG SIANTAR - Era Zana Nisa; Yanty Gurning; Dina Aryanti; Fitri Yanti Bangun (Universitas Murni Teguh, 2026)
The prevention and control of nosocomial infections is a program that encompasses the planning, implementation, supervision, and guidance aimed at reducing the incidence of nosocomial infections in hospitals. The responsibility for this task lies with the hospital Infection Prevention and Control Nursing(IPCN) committee, established by the hospital director. This study utilized a qualitative method with a descriptive phenomenological design, employing independent interview techniques. The objective was to explain the fundamental concepts of the phenomenal experiences of Infection Prevention and Control Nurses (IPCN) in implementing the IPC program at Vita Insani General Hospital, Pematang Siantar. The population in this study consisted of IPCN, with samples selected using a purposive sampling technique, involving a total of 5 participants. Data collection instruments included a voice recorder, interview guides, and field notes. Data were analyzed using NVivo version 12.0 trial. The results of this study identified four main themes: the optimal implementation of the IPCN program, receiving support in the IPCN program, experiencing obstacles, and expectations in the implementation of the IPCN program. The first theme, the IPCN program, included categories of employee health, isolation precautions, bundle implementation, education and training, rational antibiotic use, and surveillance. The second theme, management support, consisted of the category of support in the implementation of the IPCN program. The third theme, addressing substandard behaviors, involved categories originating from physicians, patients, and staff nurses. The fourth theme, expectations of the IPCN, included categories where everyone cares about IPCN, the IPCN program runs effectively, all hospital staff at Vita Insani implement IPCN, and all residents and visitors at Vita Insani can adhere to IPCN. It is recommended to further develop nursing research, where the data found in this study can be utilized as valuable input for future investigations. Abstrak Pencegahan pengendalian infeksi nosokomial adalah program yang meliputi perencanaan, pelaksanaan, dan pengawasan serta pembinaan dalam upaya menurunkan angka kejadian infeksi nosokomial di rumah sakit dan yang bertanggung jawab terhadap tugas tersebut adalah komite/panitia pencegahan dan pengendalian infeksi rumah sakit yang di bentuk oleh kepala rumah sakit. Penelitian ini menggunakan metode kualitatif dengan desain fenomenologi deskriptif dan menggunakan teknik Independeth Interview, dengan tujuan menjelaskan konsep yang mendasar dari suatu fenomena pengalaman perawat IPCN dalam pelaksanaan program PPI di RSU Vita Insani Pematang Siantar. Populasi dalam penelitian ini adalah perawat IPCN dengan pengambilan sampel menggunakan teknik purposive sampling dengan jumlah partisipan sebanyak 5 orang. Instrumen pengumpulan data menggunakan Voice Recorder, panduan wawancara dan catatan lapangan. Data dianalisis dengan Nvivo versi12.0 trial. Hasil penelitian ini didapatkan 4 tema yaitu penerapan program PPI sudah berjalan optimal, mendapatkan dukungan dalam program PPI, mengalami hambatan, dan memperoleh harapan dalam pelaksanaan program PPI. Tema pertama program PPI dengan kategori kesehatan karyawan, kewaspadaan isolasi, pelaksanaan bundles, pendidikan dan pelatihan, penggunaan antibiotik yang rasional, dan survailens. Tema kedua dukungan dari management dengan kategori dukungan dalam pelaksanaan program PPI..Tema ketiga mengubah perilaku buruk dengan kategori dari dokter, dari pasien, dari perawat pelaksana. Tema keempat harapan dari perawat IPCN dengan kategori semua orang care terhadap PPI, program PPI bisa berjalan dengan baik, semua pegawai di rumah sakit Vita Insani akan melaksanakan PPI, dan seluruh penghuni dan masyarakat yang ada di Vita Insani bisa menerpkan PPI..Saran dapat mengembangkan riset keperawatan dimana data yang di temukan dalam penelitian ini dapat di gunakan sebagai masukan untuk penelitian selanjutnya.